Modeling the influences of composition and thermal process conditions in the decimal reduction of times of Escherichia coli (ATCC 25922) in sweet orange juice - Caballero, Sheree Lee (2007)
ABSTRACT The study investigated the specific and interactive effects of dilution, brix (soluble solids), temperature and pectin on the thermal inactivationof Escherichia coli (ATCC 25922) in a citrus juice model system (CMS) through a response surface model. The CMS combinations were set using a Composite Rotatable Design with variable ranges of 20-60% dilution, 15-25°Brix, 60-73°C and 1-3% pecin. Statistical values obtained proved its reliability and accuracy (R = 0.93, R^2 = 86.98%, aR^2 = 84.65%, and %CV = 21.0179). Temperature had the greatest effect on the thermal process while increasing dilution increases its lethal effect. However, brix exhibited a protective effect, increasing the lag time of the microbial growth curve. Pectin initially caused an anti-microbial effect until 2% addition. Increased amounts caused an increase in D-value due to its ability to increase viscosity of the CMS. Validation of the predictive model proved that the predicted model over-estimated the actual response. Performance indexes (Af and Bf) obtained were within the acceptable range, providing the model's reliability. This study suggested that other strains of Escherichia coli or Leuconostoc species, reported to thrive in high-acid foods, be used. The effect thermal process to the aesthetic appeal of the CMS and its sensory qualities may also be considered